Should the dead sea be sustainable?: Investigating environmental issues using a case study. (2nd July 2016) - Saunders, Cheston Andrew
ABSTRACT: Many students leave the environmental science classroom with misconceptions centered on the availability of natural resources such as water. This article presents a case study where students assume the roles of various stakeholders and articulate their position on whether or not to pipe water from the Red Sea to the Dead Sea. Additionally, students develop an awareness of local environmental issues.